Full 15N tracer accounting to revisit major assumptions of 15N isotope pool dilution approaches for gross nitrogen mineralization. (February 2018) - Braun, Judith; Mooshammer, Maria; Wanek, Wolfgang; Prommer, Judith; Walker, Tom W.N.; Rütting, Tobias; Richter, Andreas
Abstract: The 15 N isotope pool dilution (IPD) technique is the only available method for measuring gross ammonium (NH4 + ) production and consumption rates. Rapid consumption of the added 15 N-NH4 + tracer is commonly observed, but the processes responsible for this consumption are not well understood. The primary objectives of this study were to determine the relative roles of biotic and abiotic processes in 15 N-NH4 + consumption and to investigate the validity of one of the main assumptions of IPD experiments, i.e., that no reflux of the consumed 15 N tracer occurs during the course of the experiments. We added a 15 N-NH4 + tracer to live and sterile (autoclaved) soil using mineral topsoil from a beech forest and a grassland in Austria that differed in NH4 + concentrations and NH4 + consumption kinetics. We quantified both biotic tracer consumption (i.e. changes in the concentrations and 15 N enrichments of NH4 +, dissolved organic N (DON), NO3 − and the microbial N pool) and abiotic tracer consumption (i.e., fixation by clay and/or humic substances). We achieved full recovery of the 15 N tracer in both soils over the course of the 48 h incubation. For the forest soil, we found no rapid consumption of the 15 N tracer, and the majority of tracer (78%) remained unconsumed at the end of the incubation period. In contrast, the grassland soil showed rapid 15 N-NH4 + consumption immediately after tracer addition, which was largely due to both abiotic fixation (24%) and biotic processes, largely uptake by soil microbes (10%) and nitrification (13%). We found no evidence for reflux of 15 N-NH4 + over the 48 h incubation period in either soil. Our study therefore shows that 15 N tracer reflux during IPD experiments is negligible for incubation times of up to 48 h, even when rapid NH4 + consumption occurs. Such experiments are thus robust to the assumption that immobilized labeled N is not re–mobilized during the experimental period and does not impact calculations of gross N mineralization. Graphical abstract: Highlights: Major assumptions of 15 N pool dilution approaches for gross N mineralization tested. Full recovery of 15 N-NH4 + in soil achieved over 48 h of incubation. Biotic and abiotic processes responsible for 15 N-NH4 + consumption in soils. 15 N tracer reflux negligible for incubation times up to 48 h. Constant pool dilution rates found between 2 and 24 h.